Effects of different game-based physical activity programs on body composition in Chinese preschool children - Qu, Sha; Feng, Yueyu; Song, Wenjing; Wang, Zihao; Gao, Zan; Zhao, Xing (Frontiers in Public Health, 2025)
BackgroundChildhood obesity is a growing public health concern, with preschool obesity rates in China reaching 10.4%. Physical activity (PA) is crucial for childhood obesity prevention, yet many children fail to meet recommended PA levels. Existing research primarily examines BMI rather than a detailed analysis of body composition, with sex differences remaining uncertain. This study explores the effects of different 8-week PA interventions (LPA vs. MVPA) on body composition in Chinese preschoolers, offering valuable insights for early obesity prevention.MethodsThis study utilized a two-arm experimental design with repeated measures, involving 86 preschool children from Beijing, China. Participants were randomly assigned to either the LPA or MVPA group and participated in an 8-week intervention, consisting of three 30-min sessions per week. Body composition was assessed pre- and post-intervention using bioelectrical impedance analysis (BIA), while dietary intake was evaluated through 24-h dietary recalls. Data analysis mainly included repeated-measures MANCOVA, with dietary intake controlled as a covariate.ResultsThere were no significant interaction effects of Group × Time, and Group × Time × Sex for any variables. A small but significant Sex × Time interaction for BMI was detected (F (1,71) = 4.41, p = 0.04, ηp2 = 0.06). There was no significant group effect for any variable. Significant time effects were observed for total body water (TBW) (p < 0.01, ηp2 = 0.17), skeletal muscle mass (SMM) (p < 0.01, ηp2 = 0.18), body fat mass (BFM) (p < 0.01, ηp2 = 0.11), percent body fat (PBF) (p = 0.04, ηp2 = 0.06), fat-free mass (FFM) (p < 0.01, ηp2 = 0.23), and FFM of Trunk (p = 0.05, ηp2 = 0.05). Significant sex effects were observed. Boys demonstrated higher BMI, TBW, SMM, FFM, FFM of Right Arm, FFM of Left Arm, FFM of Trunk, FFM of Right Leg, and FFM of Left Leg than girls at both time points.ConclusionPA showed a positive effect in preventing excessive BMI growth in boys, with MVPA potentially preventing the rapid accumulation of body fat. Compared to LPA, MVPA appears to yield greater benefits in increasing TBW, SMM, and FFM, while also being more effective in preventing rapid increases in BFM and PBF among preschool children. For girls, engaging in vigorous PA may be crucial for effectively enhancing body composition development.